Pengaruh Keselamatan Dan Kesehatan Kerja Terhadap Motivasi Kerja Serta Dampaknya Pada Kinerja Karyawan Bagian Proyek Kubah Masjid Pada CV. Sido Harind Pekanbaru - Herman, Herman; harwina, Yulia (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
This research aims to determine the direct and indirect influence of occupational safety and occupational health variables on employee performance through work motivation for the mosque dome project at CV Sido Harind Pekanbaru. The source of the data obtained is secondary data. Meanwhile, the data analysis technique is Path analysis using a structural model to test direct and indirect relationships between variables, the tool used is SPSS 25. The results of the study show that the direct influence of work safety has no effect. on employee performance, while indirectly work safety through work motivation has a significant effect on employee performance. And the research results of the occupational health variable directly have a significant effect on employee performance, while indirectly occupational health through work motivation does not have a significant effect on employee performance.